1990
DOI: 10.1007/bf00058836
|View full text |Cite
|
Sign up to set email alerts
|

The biodegradation of aromatic hydrocarbons by bacteria

Abstract: Aromatic compounds of both natural and man-made sources abound in the environment. The degradation of such chemicals is mainly accomplished by microorganisms. This review provides key background information but centres on recent developments in the bacterial degradation of selected man-made aromatic compounds. An aromatic compound can only be considered to be biodegraded if the ring undergoes cleavage, and this is taken as the major criteria for inclusion in this review (although the exact nature of the enzymi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(60 citation statements)
references
References 86 publications
1
52
0
7
Order By: Relevance
“…Benzoic acid could form by decarboxylation of o-phthalic acid. Known metabolic pathway of o-phthalic acid through protocatechuic acid enters the central metabolism as succinic acid by orto-cleavage of protocatechuic acid [1,2]. This was confirmed by detection of 3, 4-PCDase enzymatic activity.…”
Section: Identification Of Naphthalene Degradation Metabolitesmentioning
confidence: 67%
See 1 more Smart Citation
“…Benzoic acid could form by decarboxylation of o-phthalic acid. Known metabolic pathway of o-phthalic acid through protocatechuic acid enters the central metabolism as succinic acid by orto-cleavage of protocatechuic acid [1,2]. This was confirmed by detection of 3, 4-PCDase enzymatic activity.…”
Section: Identification Of Naphthalene Degradation Metabolitesmentioning
confidence: 67%
“…Pathways by which mesophilic bacteria degrade aromatic hydrocarbons under aerobic conditions as well as enzymes involved in the metabolism of these hydrocarbons are well-studied [1][2][3][4]. On the other hand, little is known on the growth of thermophilic microorganisms on aromatic hydrocarbons, such as benzoic acid, cresols and phenols [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The limited spreading of petroleum hydrocarbon compounds is usually attributed to the occurrence of biodegradation. Numerous laboratory studies have confirmed that BTEX compounds can be biodegraded under aerobic (3) and anaerobic conditions (4)(5)(6). However, it is often difficult to prove biodegradation at field sites since concentration changes can also be due to physical processes such as dispersion and sorption.…”
Section: Introductionmentioning
confidence: 99%
“…Mineralization of chlorocatechols is usually achieved by an ortho-cleavage route modified for the metabolism of chloroarornatics , whereas methylaromatics are usually mineralized via metacleavage routes (Smith, 1990). The ortho-cleavage pathway modified for the metabolism of chlorocatechols was postulated to be analogous to the 3-oxoadipate pathway, and the respective ring-cleavage and cycloisomerizing enzymes to differ only in substrate specificity.…”
mentioning
confidence: 99%